The Preoperative Prognostic Nutritional Index in Hepatocellular Carcinoma After Curative Hepatectomy: A Retrospective Cohort Study and Meta-Analysis. Issue 8 (22nd July 2021) - Fan, Xiaoxiao; Chen, Guoqiao; Li, Yirun; Shi, Zhaoqi; He, Lifeng; Zhou, Daizhan; Lin, Hui
Abstract: Objective: Conflicting results existed about the role of prognostic nutritional index (PNI) for hepatocellular carcinoma (HCC) patients who received curative hepatectomy. The aim of this study is to identify the predictive capacity of PNI for survival after hepatectomy. Methods: Preoperative PNI, neutrophil-to-lymphocyte ratio (NLR), tumor feature and clinical information of 187 patients with HCC from Sir Run Run Shaw hospital were evaluated. We also conducted a meta-analysis of seven cohort studies. Results: Our study showed that HCC patients with a low PNI of <45 had a poor recurrence-free survival (RFS) rate (hazard ratio [HR] 1.762, 95% confidence interval [CI] 1.066–2.911, p = 0.027, respectively). The 5-year OS and RFS rates of the high PNI (≥45) vs low PNI (<45) were 76.7% vs 50.1% ( p = 0.001) and 47.0% vs 28.9% ( p = 0.001), respectively. In HCC TNM I patients (n = 144), a low PNI remained an independent prognostic factor of OS and RFS (HR 2.305, 95% CI 1.008–5.268, p = 0.048; HR 2.122, 95% CI 1.149–3.920, p = 0.016). The 5-year OS and RFS rates of the high PNI vs low PNI were 81.3% vs 62.4% ( p = 0.041) and 53.4% vs 45.6% ( p = 0.013), respectively. In the pooled analysis, the data showed that a low PNI was significantly associated with poor OS and RFS (HR 2.27, 95% CI 1.03–4.07, p < 0.001 and HR 1.68, 95% CI 1.45–1.94, p < 0.001, respectively). Conclusions: The preoperative PNI was an independent prognostic factor for OS and RFS rates in HCC patients who received hepatectomy.